A study on performance of a liquid air energy storage system with packed bed units. (1st February 2018) - Peng, Hao; Shan, Xuekun; Yang, Yu; Ling, Xiang
Highlights: Thermodynamic analysis is presented for a LAES system combined with packed bed units. The LAES system round-trip efficiency is in the range 50–62%. Cold box inlet temperature and discharge pressure have significant influence on system performance. LAES system has smaller air storage volume and higher ASED compared with A-CAES system. Abstract: Energy storage is a key technology required to manage intermittent or variable renewable energy, such as wind or solar energy. In this paper a concept of an energy storage based on liquid air energy storage (LAES) with packed bed units is introduced. First, the system thermodynamic performance of a typical cycle is investigated and temperature distribution in cold boxes is discussed. Then, the effects of inlet temperature of cold boxes, charge and discharge pressures on thermal behaviors of LAES system are analyzed, as well as the system round-trip efficiency. Finally, an overall comparison between this LAES system and an adiabatic compressed air energy storage (A-CAES) system is conducted. The system could achieve a round-trip efficiency in the range 50–62% depending on the values of process conditions. The system round-trip efficiency decreases with the increase of cold box inlet temperature, and increases with the rise of charge and discharge pressures. Although the round-trip efficiency of the present LAES system is a bit lower than the A-CAES system, however, the air storage volume decreases and the air storage energy density (ASED) increases remarkably for the same operational conditions. The main conclusions draw from this work is beneficial for future LAES development in particular the combination with the packed bed units and the fit with the requirements for large-scale energy storage.